Energy pricing and demand scheduling in retail market: how microgrids' integration affects the market. Issue 3 (3rd April 2020) - Ahmadi, Fatemeh; Akrami, Alireza; Doostizadeh, Meysam; Aminifar, Farrokh
Abstract : This study proposes a single‐leader‐multi follower game to model a bilevel retail market among an aggregator and multiple microgrids to determine the optimal demand scheduling of the consumer, as well as price‐power bidding strategies of microgrids in an interactive scheme. In the lower level, microgrids which include several distributed energy resources and energy storage units, compete with each other and offer the optimal energy‐price bids such that their individual profit is maximised, while energy dispatch among their energy resources is also determined. Then, in the upper‐level problem, the aggregator leads the competition taking advantages of demand‐side management including interruptible and shiftable loads to minimise its energy payment for real‐time pricing of generation units. By means of Karush–Kuhn–Tucker optimality condition, the bilevel optimisation of Stackelberg game is reduced to a single‐level mixed‐integer linear programming problem. Moreover, impact of microgrids' integration on the retail market clearance mechanism, as well as required incentives for such integration has been discussed in a separate scenario.